2022
DOI: 10.3389/feart.2022.867979
|View full text |Cite
|
Sign up to set email alerts
|

Spinel Harzburgite-Derived Silicate Melts Forming Sulfide-Bearing Orthopyroxenite in the Lithosphere. Part 1: Partition Coefficients and Volatile Evolution Accompanying Fluid- and Redox-Induced Sulfide Formation

Abstract: We report abundances of major trace and volatile elements in an orthopyroxenite vein cutting a sub-arc, mantle-derived, spinel harzburgite xenolith from Kamchatka. The orthopyroxenite contains abundant sulfides and is characterized by the presence of glass (formerly melt) both interstitially and as inclusions in minerals, comparable with similar veins from the West Bismarck arc. The glass formed by quenching of residual melts following crystallization of abundant orthopyroxene, amphibole, and minor olivine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(34 citation statements)
references
References 113 publications
2
32
0
Order By: Relevance
“…These processes resulted in the orthopyroxenite formation. The role of harzburgite lithology, as a source of melts responsible for the formation of orthopyroxenite veins, was also highlighted by Bénard et al (2022). Without orthopyroxene dissolution, basaltic melts would remain orthopyroxene undersaturated with their movement restricted to the olivine-clinopyroxene cotectic line on schematic olivine-clinopyroxene-SiO 2 phase diagram (Kelemen, 1990).…”
Section: The Formation Of Orthopyroxenites Within Group II Composite ...mentioning
confidence: 99%
“…These processes resulted in the orthopyroxenite formation. The role of harzburgite lithology, as a source of melts responsible for the formation of orthopyroxenite veins, was also highlighted by Bénard et al (2022). Without orthopyroxene dissolution, basaltic melts would remain orthopyroxene undersaturated with their movement restricted to the olivine-clinopyroxene cotectic line on schematic olivine-clinopyroxene-SiO 2 phase diagram (Kelemen, 1990).…”
Section: The Formation Of Orthopyroxenites Within Group II Composite ...mentioning
confidence: 99%
“…The major and trace element compositional ranges of volatile-rich boninites do suggest that they derive from sources that have experienced ancient melt extraction events (Jenner, 1981;Hickey and Frey, 1982;Cameron et al, 1983;Crawford et al, 1989;Taylor et al, 1994;Sobolev and Chaussidon, 1996;Bédard, 1999;Le Bas et al, 2000;Kamenetsky et al, 2002;Reagan et al, 2009;Cooper et al, 2010;König et al, 2010;Pearce and Raegan, 2019;Coulthard et al, 2021). Furthermore, studies of sub-arc mantle peridotites have shown that both HCB and LCB endmember can be characterized by high volatile contents and an elevated oxidation state at a primitive stage (Bénard et al, 2016;Bénard et al, 2017b;Bénard et al, 2018b;Bénard et al, 2018c;Bénard et al, 2022). However, large variations in volatile contents and oxidation state are sometimes observed in boninites sampled on the ocean floor, even though they are not as primitive as those in mantle peridotites (Brounce et al, 2015;Brounce et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Underpinning this model is the hypothesis that extraction of LCB occurs after HCB in a continuous mantle depletion and fluxing process. However, recent studies of sulfidebearing orthopyroxenite veins formed from LCB in mantle peridotites from the Kamchatka and West Bismarck (Papua New Guinea) arcs have shed new light on some of the contrasting aspects of HCB versus LCB petrogenesis (Bénard and Ionov, 2012;Bénard and Ionov, 2013;Bénard et al, 2016;Bénard et al, 2018c;Bénard et al, 2022). These studies have notably outlined that LCB melt batches can be produced independently of HCB by low-degree melting (F≤5%) of spinel harzburgite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations